To determine which point is on the graph of the function \( y = (2x + 1)^2 - 4 \), we can substitute each \( x \) value from the given points into the equation and see if we obtain the corresponding \( y \) value.
-
For the point \( (-1, -5) \): \[ x = -1 \implies y = (2(-1) + 1)^2 - 4 = (-2 + 1)^2 - 4 = (-1)^2 - 4 = 1 - 4 = -3 \]
The calculated \( y \) value is \( -3 \), so the point \( (-1, -5) \) is not on the graph.
-
For the point \( (-1, -3) \): \[ x = -1 \implies y = (2(-1) + 1)^2 - 4 = (-2 + 1)^2 - 4 = (-1)^2 - 4 = 1 - 4 = -3 \]
The calculated \( y \) value is \( -3 \), so the point \( (-1, -3) \) is on the graph.
-
For the point \( (0, -2) \): \[ x = 0 \implies y = (2(0) + 1)^2 - 4 = (0 + 1)^2 - 4 = (1)^2 - 4 = 1 - 4 = -3 \]
The calculated \( y \) value is \( -3 \), so the point \( (0, -2) \) is not on the graph.
Therefore, the only point that lies on the graph of the function \( y = (2x + 1)^2 - 4 \) is:
\((-1, -3)\).